(untitled) (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This study is entitled A Deconstruction of John Blackthorne’s Character in the Shogun Series. The research aims to deconstruct the character of John Blackthorne and the power relations manifested through his relationship with Toranaga in the Shogun series. The theoretical framework employed is Jacques Derrida’s theory of deconstruction (1967). The data for this study were sourced from the Shogun series created by Rachel Kondo and Justin Marks. Data collection was conducted using documentation and literature review methods. To analyze the data, this study utilized a descriptive qualitative method, while the results of the data analysis are presented informally. The findings reveal that John Blackthorne’s character undergoes significant identity shifts, including Blackthorne as a representation of Western superiority, his identity transformation, and his internalization of Japanese culture. Furthermore, the study demonstrates that the power relations between Blackthorne and Toranaga are not monopolized by a single party; rather, they fluctuate based on the specific context and interests of each character. This dynamics is evidenced by the binary opposition of power relations between Blackthorne and Toranaga, the degradation of Blackthorne’s power, and the aporia within the power relations between Toranaga and Blackthorne.